The somatotype profile of male volleyball athletes (child, youth and adult) and the relationships with physical fitness: a systematic review (Research, Society and Development, 2022)
Currently volleyball is the second most practiced sport in Brazil, athletes who practice the sport to achieve high performance, need high physiological demands determine the anthropometric and morphological characteristics of athletes. Somatotypology is a methodology used by sports science to classify athletes, considered an efficient and low-cost method that divides athletes into three components (endomorphy, mesomorphy and ectomorphy). Therefore, the present study aims to investigate in the literature whether the predominant somatotype in the youth and adult male volleyball categories and the influence on the physical fitness of athletes. Methodology: A bibliographic search was carried out in the electronic databases Bireme, Pubmed, SciELO and Google Scholar, considering publications from 1999 to 2021. From a total of 138 studies, 13 met the inclusion and exclusion criteria and all used the somatotype in addition to other anthropometric variables, the predominant somatotype among adults was mesoectomorph and in the juvenile category it ectomesoectomorph, in addition, no article performed a relationship/correlation of somatotype and anthropometric profile data with physical fitness. Although the characterization of the somatotype profile has been used in several sports, both for classification and selection of athletes, studies with the juvenile population and male adults who play volleyball are still scarce.